New Breakthroughs in Quantum Optics: Research Towards More Efficient Compressed Matter - Nitin, Mahon; Tandon, Meredith; Jonathan, Bouyea (Yayasan Adra Karima Hubbi, 2024)
In quantum physics, understanding compressed matter brought to extreme states, such as those found inside neutron stars or planetary cores, is the key to unlocking mysteries about the structure and behaviour of matter at a fundamental level. Quantum Optics, as a tool for manipulating and measuring particles on atomic and subatomic scales, offers new methods for investigating properties of compressed matter that are inaccessible through conventional techniques. This research aims to develop Quantum Optics techniques that are more efficient in characterizing and manipulating compressed materials to better understand materials' mechanical and electronic properties under extreme conditions. This research method combines laboratory experiments with sophisticated mathematical modelling techniques. The experiments involve using high-intensity lasers and ion traps to generate and measure compressed states of matter. Mathematical models, supported by computer simulations, predict experimental results and provide theoretical insight into observations. This research shows that using adapted Quantum Optics techniques can achieve greater control over compressed materials and measure their properties with unprecedented accuracy. This includes revealing electrons' behaviour under high pressure and extreme temperatures. This research concludes that innovative Quantum Optics techniques can provide new and significant insights into the properties of compressed matter. This research advances the field of Quantum Optics and expands our understanding of condensed matter physics and astrophysics. It also paves the way for developing new technologies based on the unique properties of compressed materials.